Kinesin family member 3C (KIF3C) is a novel non-small cell lung cancer (NSCLC) oncogene whose expression is modulated by microRNA-150-5p (miR-150-5p) and microRNA-186-3p (miR-186-3p) - Haiwang Liu; Ran Liu; Meiling Hao; Xing Zhao; Chunhui Li (Taylor & Francis, 2021)
This study is aimed at investigating the biological function of kinesin family member 3 C (KIF3C) in non-small cell lung cancer (NSCLC) progression and its upstream regulatory mechanism. Quantitative real-time PCR, Western blot and immunohistochemistry were adopted to examine microRNA-150-5p (miR-150-5p), microRNA-186-3p (miR-186-3p) and kinesin family member 3 C (KIF3C) expression levels. NSCLC cell proliferation, migration, and invasion were detected through cell counting kit-8 (CCK-8) assay, EdU assay, and Transwell assay. The metastasis of NSCLC cells was evaluated utilizing a pulmonary metastasis model in nude mice in vivo. The targeted relationship among KIF3C 3ʹUTR, miR-186-3p, and miR-150-5p were verified by dual-luciferase reporter gene assays. It was confirmed that in NSCLC tissues and cells, KIF3C expression level was increased and KIF3C overexpression promoted NSCLC cell proliferation and metastasis. Additionally, miR-150-5p and miR-186-3p directly targeted KIF3C to repress its expression. Our data suggest that KIF3C, which is negatively regulated by miR-150-5p and miR-186-3p, is an oncogenic factor in NSCLC progression.
Keywords: Biophysics; Biochemistry; Physical Sciences not elsewhere classified; Cell Biology; Genetics; Molecular Biology; Physiology; Biological Sciences not elsewhere classified; Cancer; Hematology